1962
DOI: 10.1172/jci104653
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Uric Acid Excretion in Gout*

Abstract: The urinary excretion of uric acid in individuals with primary gout has been shown to be approximately the same as, or in a minority of instances greater than, that of normal subjects on comparable diets (2, 3). These observations, plus the failure to demonstrate significant differences in the renal clearance of uric acid in gouty and nongouty control subjects, have led to the conclusion that patients with gout excrete uric acid in a normal manner (2-5).This view has, however, recently been challenged (6) on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1963
1963
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…These observations support suggestions previously made4 5 10 They found that at normal levels of urate in the plasma there was no significant difference between the gouty and control subjects in the excretion of urate. But at higher plasma levels of urate all but one of the gouty patients showed impairment of excretion when compared with the controls.…”
supporting
confidence: 92%
“…These observations support suggestions previously made4 5 10 They found that at normal levels of urate in the plasma there was no significant difference between the gouty and control subjects in the excretion of urate. But at higher plasma levels of urate all but one of the gouty patients showed impairment of excretion when compared with the controls.…”
supporting
confidence: 92%
“…of the control value. Following this, a number of studies attempted to assess the effect of added loads of uric acid in gouty and normal subjects and it became evident that both groups were able to increase their rate of clearance in such circumstances (Nugent and Tyler, 1959;Lathem and Rodnan, 1962;Gutman, Yu, and Berger, 1969). Data from the present study, however, indicate a rather greater difference in mean clearance figures, values for gouty patients (3 9 ml./min.)…”
Section: 'Vweight In Poundsmentioning
confidence: 99%
“…In considering the pathogenesis of this loss of diurnal rhythm for urinary pH, it is uncertain whether the excretion of acid urine throughout the day and night is primary, as part of the disturbance of uric-acid metabolism in gout, or secondary to renal damage. There has always been a controversy as to whether the renal handling of uric acid plays a primary role in the pathogenesis of gout, and recently there has been more evidence to support this concept (Nugent and Tyler, 1959 ;Lathem and Rodnan, 1962). It would not be surprising, then, to find disturbances of other tubular functions.…”
Section: Discussionmentioning
confidence: 99%